The division of housework. Does regional context matter? - Trude Lappegård; Randi Kjeldstad; Torbjørn Skarðhamar (Statistics Norway, Research Department, 2012)
This study investigates the relationship between the division of housework in couples and the local gender equality context. We use data from the Norwegian Generations and Gender survey 2007 combined with a range of macrolevel measures on gender equality in the municipality where the respondents live. Results show that in married and cohabiting couples, the division of housework is associated with local gender equality context. Irrespective of their individual characteristics, couples living in municipalities with high gender equality have more equal division of housework. The within country regional variation in women's status and participation on various arenas as compared to men's, seems to influence housework arrangements in the family. This corresponds to findings from previous studies comparing countries, hence indicating that several of the operating mechanisms are also present at a lower aggregate level. However, in contrast to cross-national comparisons, we find that individual characteristics are not associated differently with the division of housework according to regional gender context. This might be due to the fact that Norway is a relatively homogeneous and egalitarian country at both the regional and individual level.
Keywords: J22; 330; division of housework; regional gender equality index; multilevel analysis; Norway